What is Behind Extreme Negative Returns co-movement in the South Eastern European Stock Markets? - Dragan Tevdovski; Viktor Stojkoski (Scientific Annals of Economics and Business, 2021)
This paper examines co-movement of extreme returns in eight South Eastern European (SEE) stock markets during the period covering both the financial crisis from 2007-2009 and the COVID-19 health crisis. The analysis is based on coexceedances which represent the number of joint occurrences of extreme returns in a group of stock market indexes. To provide a valuable insight on how persistence, asset class, and volatility effects are related with the coexceedances, we utilize a multinomial logistic regression procedure. We find evidence in favour of the continuation hypothesis. However, the factors associated with the coexceedances differ between the SEE European Union (EU) members and the SEE EU accession countries. The EU members are more dependent on signals from major EU economies, while the accession countries are mainly impacted by regional signals. The implications of our analysis may help policy makers in understanding the nature of shock transmission in SEE stock markets.